THE EXPERIENCES OF ADOLESCENTS ORPHANED BY HIV/AIDS-RELATED CONDITIONS - Louw, Lynette; Joubert, Kotie (Social Work/Maatskaplike Werk, 2007)
The work environment of social workers in South Africa is riddled with new and complex social problems, often draining the available resources (Giese, Meintjes, Croke & Chamberlain, 2003:7). Personnel in rural areas are confronted with huge numbers of orphaned children in need of urgent statutory intervention, mostly because of the economic burden brought about by their “orphan” status. Very little time can be spent on the socio-emotional care of these children, as the emphasis largely falls on the provision of basic needs, such as grants, school uniforms and food.